Harmful or Beneficial to Humans and the Environment? An Empirical Study on the Social Acceptance and Risk Perception of CO2-Based Fuels - Anika Linzenich; Linda Engelmann; Katrin Arning; Miaomiao Du; Sebastian Heger; Martina Roß-Nickoll; Martina Ziefle (Frontiers in Environmental Science, 2022)
Risk analysis and assessment of toxic effects are important elements to be considered in the development of renewable fuels, such as CO2-based fuels made from CO2, water, and renewable energy. However, the successful introduction of CO2-based fuels could also be affected by public concerns about possible risks and adverse effects on health and the environment. In order to examine risk perceptions of laypeople for CO2-based fuels and to understand if they can act as a barrier for the public acceptance of these fuels, we carried out an online survey with German laypeople. A special focus was placed on perceptions of toxic effects such as beliefs about exposure pathways and resulting health impacts, but also on participants’ openness towards CO2-based fuels. Results showed that CO2-based fuels were seen as an acceptable and beneficial technology and risks were perceived to be low. By tendency, lower risk perceptions were related to a higher acceptance of CO2-based fuels. The overall risk judgment was impacted by fears about toxic effects, concerns about environmental pollution, and the perceived general harmfulness of CO2-based fuels. The general openness towards CO2-based fuels was revealed to affect risk perceptions and beliefs about toxic effects: A higher openness towards the topic was linked to less severe concerns about CO2-based fuels. The findings from this study provide valuable insights on how to develop communication concepts to inform laypeople about possible risks and benefits of CO2-based fuels to address their concerns and information demands and give them a better understanding of the effects of toxic substances on different risk targets.